Upaya Mengatasi Kesulitan Belajar Siswa dalam Sistem Hukum Peradilan Internasional - Herlina Ariani (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2015)
The subject of this research is 42 persons of students at class of Social Science-3 grade XI of SMA 12 of Medan in the 2012/2013 school year. This research purposes to elevate learning result by using method of inquiry on the subject of Civic Education in the class of Social Science-3 grade XI of SMA 12 of Medan in the 2012/2013 school year. Learning method which used is inquiry method. The collecting data instrument are observation, interview, essay test, and multiple choice test at the last cylcle of every treatment to the class have done. This research consists of two cycles which are the first and second cycle consists of problems, phase of planning, implementing, observing, data analysing, and reflecting phase. The result of research represents that using the inquiry method on the subject of Civic Education can be increase students’ learning results. It obvious by seeing average of first test score of 52.02 with 11.09 percent completing of learning. However after implementing the first treatment by inquiry method, achievement of average score elevated on 63.80 with 45.24 percent completing of learning. Then at the second cylce, achievement of average score elevated on 75.12 with 92.85 percent completing of learning.  Therefore can be concluded that by using inquiry method on the subject of Civic Education could be increase learning result of students at SMA 12 of Medan.